Development of CAR-T Cell Persistence in Adoptive Immunotherapy of Solid Tumors - Fan, Jiaqiao; Das, Jugal Kishore; Xiong, Xiaofang; Chen, Hailong; Song, Jianxun (Frontiers in Oncology, 2021)
Chimeric antigen receptor (CAR) T (CAR-T) cell transfer has made great success in hematological malignancies, but only shown a limited effect on solid tumors. One of the major hurdles is the poor persistence of infused cells derived from ex vivo activation/expansion and repeated antigen encounter after re-infusion. Bcl-xL has been demonstrated to play an important role on normal T cell survival and function as well as genetically engineered cells. In the current study, we developed a retroviral CAR construct containing a second-generation carcinoembryonic antigen (CEA)-targeting CAR with the Bcl-xL gene and tested the anti-CEA CAR-T cell immunotherapy for colorectal cancer. In vitro, the anti-CEA CAR-T cells dramatically destroyed CEA-expressing tumor cells and sustained survival. In vivo, adoptive cell transfer of anti-CEA CAR-T cells significantly enhanced the ability of the CAR-T cells to accumulate in tumor tissues, suppress tumor growth and increase the overall survival rate of tumor-bearing mice in a murine model of colorectal cancer. These results demonstrate a novel CAR-T platform that has the ability to increase the persistence of CAR-T cells in solid tumors through exogenous expression of persistent genes. The data provide a potentially novel approach to augment CAR-T immunotherapy for solid tumors.